Strong Truncated Matrix Moment Problem of Hamburger - Simonov, K. K. (Sarajevo Journal of Mathematics, 2024)
In this paper we consider the strong truncated matrix moment problem on the real line. We describe all the solutions of the problem in the form of a Nevanlinna type formula. We use M. G. Kreĭn's theory of representations for Hermitian operators and the technique of boundary triplets and the corresponding Weyl functions. 2000 Mathematics Subject Classification. 44A60; 47A57, 42C05